Война 1812 года - Лубченков Ю. Н. (История России, 2011)
5-6 кл. Экземпляры: ф-21 (ретроконверсия) / Инвентарный номер: 47191 / Цена: 220.00 / Сис.шифр: 63.3(2)4 / Авт.знак: Л 82 / ГРНТИ: 03 / ББК: 63.3(2)47